Algal biomusic generation - Joshua M. Lawrence; Emma Albertini; Alberto Scarampi; Paolo Bombelli; Lucia B. Giron; Lena Kuzmich; Christopher J. Howe (Applied Phycology, 2025)
Technologies which can generate music with limited human intervention are a longstanding area of investigation for musicians and musicologists, with particular interest in how these technologies can be harnessed for ecocentric forms of musical expression. To date, most of these efforts have focused on the use of computational algorithms to compose music. Biomusic – music created using biological data – provides an alternative paradigm for the creation of non-human music which can be truly ecocentric. Photosynthetic organisms in particular offer the ability to create music which responds to changes in their environment, such as changes in light conditions and temperature. Herein, we propose how the ubiquitous bioelectrical activities of algae (which are correlated with their photosynthetic activity) can be utilized for biomusic generation. In addition to describing the scientific principles underpinning these algal biomusic systems, we also provide tutorial descriptions of the bioelectrochemical devices and signal processing pipelines which can be used to engineer them. In addition, we provide an overview of the many musical applications that can be accessed with this technology, highlighting a few pioneering examples of algal biomusic generation.